INTRANASAL KETAMINE FOR PROCEDURAL SEDATION. Issue 9 (14th August 2014) - Hall, Dani; Robinson, Alison
Abstract : Objectives & Background: The safety of intravenous ketamine in procedural sedation is well described. 1 2 Guidelines produced by NICE 3 and the College of Emergency Medicine 4 are used by Emergency Departments (ED) nationwide. To avoid cannulation, opioids are frequently administered to children intranasally 5, avoiding first-pass metabolism. 6 Intranasal ketamine (INK) is an effective analgesic in children 7 and has been successfully utilised in prehospital and military settings. 8 9 However, a recent survey revealed that INK is not currently in use in UK paediatric EDs. 10 To determine the current level of evidence of the use of INK in procedural sedation in children we developed a clinical scenario and three part question. A 4 year old child presents with a lip laceration. Options for closure are under procedural sedation in the ED or general anaesthetic in theatre. You feel he would be suitable for procedural sedation. Your department's policy is intravenous ketamine. However the child is very upset and you feel the trauma of cannulation will adversely affect quality of sedation. Would INK be an alternative? Methods: In [children undergoing procedural sedation] does [intranasal ketamine] result in [rapid onset, safe, effective sedation without prolonged recovery]? Using the search strategy outlined in table 1, seven relevant papers were identified. 11–18 Results: Efficacy INK can be successfully used to sedate children for dental procedures at 3–6 mg/kg. 11–13 5 mg/kg facilitates cannulation prior to induction of anaesthesia. 14–16 An ED based double-blinded RCT compared sedation with 3, 6 and 9mg/kg INK 17 . The study was small and was terminated early due to high sedation failures. Safety All studies demonstrated 3–9 mg/kg INK is safe, with no serious adverse events. Efficiency At 3–9mg/kg, time to onset ranged from 3.6–9.4 minutes with recovery time between 30–69 minutes. 11–17 Conclusion: An ideal agent for procedural sedation in the Paediatric ED is safe, easily delivered with rapid onset and recovery. The limited but growing evidence supports the use of INK to achieve this, although ideal dose is still unclear. All published studies to date have varying flaws with strict protocols defining adequate sedation and a lack of validated dissociative sedation scale potentially limiting reported success. More studies are emerging with a recent proposal presented to the PERUKI group. INK may still make its way into Paediatric EDs in the not too distant future.